Investigation of HDAC8-ligands' intermolecular forces through molecular dynamics simulations: profiling of non-bonding energies to design potential compounds as new anti-cancer agents. Issue 13 (2nd September 2021) - Dewaker, Varun; Srivastava, Ajay K.; Arora, Ashish; Prabhakar, Yenamandra S.
Abstract: Histone deacetylases are zinc-dependent isoform enzymes and play important role in cellular homeostasis. Among these, HDAC8 is a potential anticancer drug target. To design new inhibitors using protein-ligand energy profiles, an all atom molecular dynamics (MD) simulations were carried out on nine HDAC8-ligand co-crystals (PDBs: 1T64, 1T69, 1T67, 3F07, 1W22, 1VKG, 5FCW, 3SFF and 3SFH). TSN, SHH, B3N, AGE, NHB, CRI, 5YA, 0DI and 1DI are ligands of PDBs, respectively. For these HDAC8-ligands, relative Gibbs binding free energy (Δ G bind ) from MM/PBSA method and non-bonding energies (NBE) are in agreement with each other ( r 2 =0.678). Therefore, the NBEs are used to analyze ligands' sub-structures, namely zinc-binding, linker and CAP groups. For linker/CAP regions, this identified carbonyl, amide, and sulfonamide moieties as desirable and alkyl/aryl moieties as electrostatically unfavourable. Using this information, systematically new compounds were designed and subjected to MD simulations. This resulted in seven compounds (NC-I to NC-VII ) with encouraging energy profiles (NBE: −76.25 to −127.09 kcal/mol; Δ G bind : −17.21 to −57.42 kcal/mol) in comparison to that of the HDAC8 ligands (NBE: −46.25 to −106.29 kcal/mol; Δ G bind : −14.74 to −49.52 kcal/mol). From these, NC-VI showed best energy profile (NBE = −126.15 kcal/mol; Δ G bind = −57.42 kcal/mol) suggesting its binding affinity and thermodynamic stability. In addition to this, NC-II and NC-III have shown promising NBE and Δ G bind profiles. These may serve as lead molecules for exploration against HDAC8 in cancer therapy. This has provided a basis for designing new compounds with improved NBE and ΔGbind profiles by modifying the unfavourable or not so favourable regions of ligands. Communicated by Ramaswamy H. Sarma